Saints across Traditions and Time Periods: Methods for Increasing Range and Reading in Comparative Frameworks - French, Todd E. (Religions, 2019)
This paper offers a nascent attempt at best practices for the comparative method in a conference setting. Exploring the value in transcendence of traditions and specialization, it traces the preparation and outcome of a recent comparative hagiology panel and develops a list of possible steps for facilitating meaningful interchange between scholars. Building on Freiberger's methodology for Comparative Religions, it applies a method specifically to hagiographical studies.